Analisis Kesesuaian Lahan Lanskap Wisata Pantai Lenggoksono Berbasis Sistem Informasi Geografi Desa Purwodadi, Kabupaten Malang - Debora Budiyono; Hendra Kurniawan; Astri Sumiati; Hendrikus Ngaga (Jurnal Lanskap Indonesia, 2023)
Purwodadi Village is located in Malang Regency, East Java which has the potential of a very beautiful coastal landscape as a tourist attraction. One of the advantages of Purwodadi Village is that there is a Lenggoksono beach which has natural and cultural potential as a tourist attraction. However, currently the development of the Lenggoksono beach tourism area has not been accompanied by an analysis of land suitability as a tourist attraction. The purpose of the research is to analyze the sustainable land suitability of the Lenggoksono coastal tourism landscape in Purwodadi Village, Malang Regency. The method used is field observation and interviews with the Malang district government. Data analysis is the physical aspect consisting of topographic analysis, beach width, beach type, water base material, beach depth, water brightness, coastal slope, current speed, dangerous biota, fresh water availability, and vegetation. Data analysis was carried out spatially with a land cover approach through a Geographic Information System (GIS). The results showed that the land suitability of the Lenggokson beach tourism area was classified as potential with an area of ​​10.6 ha (52.8%) and quite potential with an area of ​​9.5 ha (47.2%) of the total area of ​​21.1 ha. This shows that the Lenggoksono beach area has the potential to be developed as a sustainable beach tourism landscape by considering the carrying capacity of the area.